Power and Color Doppler Ultrasound Settings for Inflammatory Flow: Impact on Scoring of Disease Activity in Patients With Rheumatoid Arthritis. Issue 2 (February 2015) - Torp‐Pedersen, Søren; Christensen, Robin; Szkudlarek, Marcin; Ellegaard, Karen; D'Agostino, Maria Antonietta; Iagnocco, Annamaria; Naredo, Esperanza; Balint, Peter; Wakefield, Richard J.; Torp‐Pedersen, Arendse; Terslev, Lene
<x xml:space="preserve">Abstract</x> Objective To determine how settings for power and color Doppler ultrasound sensitivity vary on different high‐ and intermediate‐range ultrasound machines and to evaluate the impact of these changes on Doppler scoring of inflamed joints. Methods Six different types of ultrasound machines were used. On each machine, the factory setting for superficial musculoskeletal scanning was used unchanged for both color and power Doppler modalities. The settings were then adjusted for increased Doppler sensitivity, and these settings were designated study settings. Eleven patients with rheumatoid arthritis (RA) with wrist involvement were scanned on the 6 machines, each with 4 settings, generating 264 Doppler images for scoring and color quantification. Doppler sensitivity was measured with a quantitative assessment of Doppler activity: color fraction. Higher color fraction indicated higher sensitivity. Results Power Doppler was more sensitive on half of the machines, whereas color Doppler was more sensitive on the other half, using both factory settings and study settings. There was an average increase in Doppler sensitivity, despite modality, of 78% when study settings were applied. Over the 6 machines, 2 Doppler modalities, and 2 settings, the grades for each of 7 of the patients varied between 0 and 3, while the grades for each of the other 4 patients varied between 0 and 2. Conclusion The effect of using different machines, Doppler modalities, and settings has a considerable influence on the quantification of inflammation by ultrasound in RA patients, and this must be taken into account in multicenter studies.